Tetrazole-Based Probes for Integrated Phenotypic Screening, Affinity-Based Proteome Profiling, and Sensitive Detection of a Cancer Biomarker - Cheng, Ke; Lee, Jun-Seok; Hao, Piliang; Yao, Shao Q.; Ding, Ke; Li, Zhengqiu (John Wiley & Sons Ltd., 2017)
Target-identification phenotypic screening has been a powerful approach in drug discovery; however, it is hindered by difficulties in identifying the underlying cellular targets. To address this challenge, we have combined phenotypic screening of a fully functionalized small-molecule library with competitive affinity-based proteome profiling to map and functionally characterize the targets of screening hits. Using this approach, we identified ANXA2, PDIA3/4, FLAD1, and NOS2 as primary cellular targets of two bioactive molecules that inhibit cancer cell proliferation. We further demonstrated that a panel of probes can label and/or image annexin A2 (a cancer biomarker) from different cancer cell lines, thus providing opportunities for potential cancer diagnosis and therapy.
Keywords: PHOTO-CROSS-LINKERS; SMALL-MOLECULE PROBES; PHOTOAFFINITY LINKERS; TARGET IDENTIFICATION; KINASE INHIBITORS; HUMAN-CELLS; ANNEXIN A2; BINDING; DISCOVERY; PROTEINS